2022
DOI: 10.1002/fsn3.2728
|View full text |Cite
|
Sign up to set email alerts
|

Fate of aflatoxins M1 and B1 within the period of production and storage of Tarkhineh: A traditional Persian fermented food

Abstract: In 21st century, food products containing aflatoxins above the maximum residue limit have been the center of debate throughout the world since they endanger human healthy lifestyle and commodities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Indeed, it was reported that Kefir was able to adsorb AFB1 and consequently reduce their toxicity Ben Taheur et al, 2017). Previous studies reported a significant correlation between pH reduction and AFB1 breakdown, since the production of organic acids and other fermentation by-products can detoxify AFB1 (Moradi et al, 2022).…”
Section: Antioxidant Enzymes and Lipid Peroxidationmentioning
confidence: 99%
“…Indeed, it was reported that Kefir was able to adsorb AFB1 and consequently reduce their toxicity Ben Taheur et al, 2017). Previous studies reported a significant correlation between pH reduction and AFB1 breakdown, since the production of organic acids and other fermentation by-products can detoxify AFB1 (Moradi et al, 2022).…”
Section: Antioxidant Enzymes and Lipid Peroxidationmentioning
confidence: 99%
“…Fermented dairy–cereal‐based foods can provide valuable bioactive compounds that contain sufficient essential amino acids due to the presence of milk protein, which compensates for the deficiency of essential amino acids such as lysine and threonine in cereals and promotes consumer health (Mashak et al., 2014 ). Doowina in Kurdish or Tarkhineh, Tarkhowana, Tarhana in Turkish, one of the local products of the western regions of Iran (Kermanshah, Ilam, Kurdistan, Lorestan, and Hamedan), is made from the fermentation of wheat flour, salt, and concentrated ayran (drinking yogurt) (Moradi et al., 2022 ). It tastes like sour wheat bread.…”
Section: Introductionmentioning
confidence: 99%
“…and threonine in cereals and promotes consumer health (Mashak et al, 2014). Doowina in Kurdish or Tarkhineh, Tarkhowana, Tarhana in Turkish, one of the local products of the western regions of Iran (Kermanshah, Ilam, Kurdistan, Lorestan, and Hamedan), is made from the fermentation of wheat flour, salt, and concentrated ayran (drinking yogurt) (Moradi et al, 2022). It tastes like sour wheat bread.…”
mentioning
confidence: 99%